Cholesterol Granuloma in the Maxillary Sinus: Are Endodontically Treated Teeth Involved in Its Etiopathogenesis? - Silas Antonio Juvencio de Freitas Filho; Gilberto Gallo Esteves; Denise Tostes Oliveira (Case Reports in Pathology)
Cholesterol granuloma (CG) is a tissue reaction in response to the accumulation of cholesterol crystals rarely found in the maxillary sinus. The etiopathogenesis of maxillary sinus CG remains unclear. We reviewed the literature and added two new reports of cholesterol granuloma in maxillary sinus related to endodontically treated maxillary posterior teeth. The first report refers to a 45-year-old woman diagnosed with rhinitis, who was submitted to endodontic retreatment of maxillary molar, and subsequently showed maxillary sinus opacity with cystic appearance. The second case describes a young adult woman, who presented a cystic mass in maxillary sinus after endodontic treatment, in close association with the apex of the maxillary right second premolar. Both patients were treated by a classic Caldwell-Luc surgery and the microscopic analyses revealed maxillary sinus CG. In the following, the authors discuss the probable involvement of endodontically treated maxillary posterior teeth in the etiopathogenesis of maxillary sinus CG.